A role for surgery in the treatment of relapsed Hodgkin lymphoma. Issue 1 (8th October 2018) - Fahy, A.S.; Kong, I.; Weitzman, S.; Dix, D.; Baruchel, S.; Gerstle, J.T.
Abstract: Treatment of Hodgkin lymphoma (HL) has advanced over time, rendering a fatal disease now largely curable. Multiagent chemotherapy regimens, hematopoietic stem cell transplantation, and radiotherapy are the mainstays of care. Surgical intervention is rarely indicated other than for biopsy at diagnosis. However, for patients with recurrent relapsed HL isolated to one anatomical location, refractory to all other therapy, there may be a beneficial role for surgical excision. Herein, we report the surgical management of three relapsed patients with stage IVB HL who were refractory to multiple other therapeutic approaches, who all achieved good event‐free survival after operative management.